Analysis of Rigid Steel Frames With and Without Bracing Systems under the Effect of Wind Loads in Maysan Province. - Dr.Abbas Oda Dawood / Ameen Ismael Atya ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Analysis of rigid steel frame with and without X- bracings at corners subjected to along wind loads in the Maysan province is presented. The nonlinear analysis using P-delta effect is accomplished by SAP 2000 V16 program. The basic wind speed for analysis purposes is specified according to Iraqi standards IQ 301. The static wind loads on the building is determined according to ACSE 7-05 standards. The main objective of this study is to investigate the effect of X-bracing system on the behavior a 12-storysquare rigid frame multi-story steel building. Variations of base shear, base moment, drift ratio, torsion bending moment, axial stresses, bending stresses, shear stress, axial force, shear force and displacement are considered for discussion and comparison. Its concluded that the presence of X-bracings is reduced the drift or lateral displacement by about 20% and also reduced the base moment by about 5% due to smaller drift led to smaller additional base moment due to P-Delta effect. Thus for rigid frame steel structure with up to 12 stories subjected to wind in Maysan province, the x-bracings is effective in stability and serviceability requirements.